Application of fano resonance effects in optical antennas formed by regular clusters of nanospheres - Emami, S.D.; Soltanian, M.R.K.; Attaran, A.; Abdul-Rashid, H.A.; Penny, R.; Moghavvemi, Mahmoud; Harun, Sulaiman Wadi; Ahmad, Harith; Mohammed, W.S. (Springer Verlag (Germany), 2015)
This paper describes an analytical model developed to study the Fano resonance effect in clusters of spherical plasmonic nanoparticles under local excitation. The model depicted the case of a parallel single dipole emitter that was near-field coupled to a pentamer or heptamer cluster of nanospheres. Spatial polarization and field distributions of the optical states and resonance spectra for these cluster configurations were calculated. It was discovered that polarization interference between the nanoparticles triggered the formation of a second peak in the directivity spectra at 690 nm, and this in turn provided a mechanism for the occurrence of subradiant mode effects. The directivity calculation was analyzed in order to qualify the redirection of emission. Performances of various nanoantennae were investigated and fully characterized in terms of spatial geometric differences and the Fano resonance effect on plasmonic nanoparticles in the optical domain. Light radiation patterns were found to be significantly affected by nanosphere sizes and positioning of nanospheres with respect to the dipole. The analytical treatment of these modeled nanoantennae yielded results that are applicable to physical design and utilization considerations for pentamer and heptamer clusters in nanoantennae mechanisms.